Comparative analysis of perioperative prophylactic antibiotics in prevention of surgical site infections in stented, distal hypospadias repair. Issue 2 (April 2021) - Canon, Stephen J.; Smith, Jacob C.; Sullivan, Elizabeth; Patel, Ashay; Zamilpa, Ismael
Summary: Purpose: There is limited evidence that prophylactic antibiotics prevent surgical site infection in stented, distal hypospadias repair. Our hypothesis is that the use of prophylactic antibiotics does not affect the rate of surgical site infection in this setting. Methods: We conducted a retrospective study of consecutive patients over a 6-year period with distal penile hypospadias treated with urethral stenting. Variables analyzed include age, type of repair, usage of preoperative and/or postoperative antibiotics, and length of follow-up. Patients with a history of proximal or re-operative hypospadias repair were excluded. Surgical site infection was defined by the presence of postoperative penile erythema and/or purulent drainage treated with therapeutic antibiotics. Secondary outcome analysis included the presence of other hypospadias complications. Results: 441 consecutive subjects met our inclusion criteria with a mean age of 13.3 months. Patients were categorized into groups: Group 1 – Preoperative antibiotics (n = 64), Group 2 – Both Preoperative & Postoperative antibiotics (n = 159), Group 3 – Postoperative antibiotics (n = 122), Group 4 – No Preoperative or Postoperative antibiotics (n = 96). Two surgical site infections were reported out of the 441 patients: 1 in Group 3 and 1 in Group 4 (p = 0.513). There was no significant difference in the total patients with a hypospadias complication between groups. In the table below, Groups 1–3 were combined (345 patients) for comparison to Group 4 (No antibiotics, 96 patients) for further analysis with no difference in SSIs (p = 0.388) or respective hypospadias complications. Conclusions: The use of perioperative prophylactic antibiotics, both before and after surgery for distal, stented hypospadias repair, have not been shown to reduce the rate of surgical site infections nor hypospadias complications. Consequently, the benefit of prophylactic antibiotics in this setting is unclear. Summary Table Surgical-related outcomes by antibiotic usage and non-usage. Summary Table Any Administration of Antibiotic (PreOp and/or PostOp) No Administration of Antibiotics P-value Number of patients (n) 345 96 Surgical site infection, n (%) 1 (0.3) 1 (1.0) 0.388 Hypospadias complications, n (%) 22 (6.4) 5 (5.2) 0.673 Urethrocutaneous fistula 17 (4.3) 3 (3.1) 0.586 Meatal Stenosis 4 (1.2) 2 (2.1) 0.615 Urethral diverticulum 1 (0.3) 0 (0.0) 0.968 Wound dehiscence 1 (0.3) 2 (2.1) 0.121 UTI 1 (0.3) 0 (0.0) 0.968